INDIKATOR KOLEKTIBILITAS KREDIT JOINT FINANCING MENGGUNAKAN OLS & LOGIT - Silalahi, Derisman; Hulu, Edison (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This study aims to determine indicators that have a significant effect on debtor collectability. The number of sample data used is 102 joint financing debtors whose loans were realized in 2019, which consists of two groups of 51 debtors that have current and non-current collectability. The analytical method used is the ordinary least square method and the logit regression method, where the combination of the two analytical methods being used at once was not yet found in previous studies. The analysis result using ordinary least squares shows three (3) significant indicators that affect collectability, namely term of the loan, value of collateral and monthly liabilities, with a significance level of 0.05. Meanwhile, the binary logit analysis results in four (4) significant indicators, namely term of the loan, value of collateral and monthly liabilities with a significance level of 0.05 and level of job risk with a significance level of 0.10. The R-squared value in the ordinary least square is 41%, which means that the ten indicators in this study simultaneously affect the collectability variable, while 59% is influenced by other variables not included in this study. The analysis using the logit regression method shows an R-square value of 39% which can be said that the ten indicators altogether affect debtor collectability by 39%.